PD-1 regulates imiquimod-induced psoriasiform dermatitis through inhibition of IL-17A expression by innate γδ low T Cells - Imai, Yasutomo (J Immunol, 2015)
Programmed cell death 1 (PD-1) is key regulatory molecule that has been targeted in human cancers, including melanoma. In clinical testing, antibodies against PD-1 have resulted in psoriasiform dermatitis (PsD). To determine if PD-1 regulates PsD, we compared skin responses of PD-1-deficient (PD-1KO) mice and wild type (WT) control in an imiquimod (IMQ)-induced murine model of psoriasis. PD-1KO mice showed severe epidermal hyperplasia, greater neutrophilic infiltration, and higher expression of Th17 cytokines (vs. WT mice). IMQ exposure increased PD-1 expression by skin γδ low (GDL) T cells and enhanced expression of PD-L1 by keratinocytes. Three-fold increases in the percentage of IL-17A(+) GDL T cells were observed in skin cell suspensions derived from IMQ-treated PD-1KO mice (vs. WT controls), suggesting that the lack of PD-1 has a functional effect not only on αβ T cells, but also on GDL T cells, and that PD-1 may play a regulatory role in PsD.